Trends on the Cellulose-Based Textiles: Raw Materials and Technologies - Felgueiras, Catarina; Azoia, Nuno G.; Gonçalves, Cidália; Gama, Miguel; Dourado, Fernando (Frontiers in Bioengineering and Biotechnology, 2021)
There is an emerging environmental awareness and social concern regarding the environmental impact of the textile industry, highlighting the growing need for developing green and sustainable approaches throughout this industry’s supply chain. Uphill, due to population growth and the rise in consumption of textile fibres, new sustainable raw materials and processes must be found. As a unique biopolymer in terms of its structure and properties, cellulose is the most important and available renewable resource for textiles. The physical and chemical modification reactions yielding fibres are of high commercial importance today. Recently developed technologies allow the production of filaments with the strongest tensile performance without dissolution or any other harmful and complex chemical processes. Fibres without solvents are thus on the verge of commercialization. In this review, the technologies for the production of cellulose-based textiles, their surface modification and the recent trends aiming at sparing the forest from massive exploitation such as the use of bacterial nanocellulose, are discussed. The life cycle assessment of several cellulose fibre production methods is also addressed.